Hardness, behavior and metal surface evaluation of recasting non-precious dental alloys - (:unkn) unknown (Trans Tech Publications Ltd, 2007)
Recasting of economic alloys can change several properties. The number of recasting was found to have negligible effect on surface texture and on the amount of corrosion products released. The methods and equipments utilized in the casting of an alloy are important on the quality of casting. Carbon incorporated in a noble or economic alloy during casting is known to affect the mechanical values of the metal. In the present study we aimed to investigate the change in structure and metal hardness due to recasting. Materials and method: The effect of recasting, up to four times of a non precious "Finalloy" commercial dental alloy on their Rocwell C hardness behavior and their microstructures was inspected. Using "Kerr casting waxes" patterns were prepared similar to the samples from "Finalloy". The investments were pre-heated to phase at temperatures between 900°C and 1000°C. The alloy was melted by an acetylene-oxygen flame in a silicate crucible and four groups were compared: New alloy and alloys casted two, three, and four times (n = 7). After casting, Brinell harnesses were recorded. Values of Rocwell C strength, for each specimen group were analyzed by one-way analysis of variance, followed by the Student-Newman-Keuls multiple range test. A metal microscope was used to evaluate the surface morphology of the samples before hardness tests. 1st Casting :30.65 ± 0.3 kgf, 2nd Casting: 31.33 ± 0.4 kgf, 3rd Casting:34.80 ± 0.3 kgf, 4 th Casting: 35.5 ± 28 kgf represents the Rocwell hardness of the castings. The results showed that hardness, increased with repeated castings. The experimental data indicates that increasing the number of successive recasting of ±Finalloy± enhances the Rocwell C hardness, thus, after remelting and recasting, the biological properties decreases. Microscope study: Increase of the carbon content on the gren bounders of a cobalt-chromium alloy causes a considerable change in its microstructure. The hardness and yield point for 0.05 %, 0.1 % and 0.2 % tensile strength and elongation were determined for these test-pieces. The results showed that hardness, yield points and tensile strength increased with increased carbon content, whereas the elongation lessened. We determined that carbon concentrated at gren bounders. The clinical importance of the study is that recasting affected the properties of the metal, for best biological results with dental alloys always new metals must be used.
Keywords: Cr-Co alloys; Economic alloys; Microstructure; Recasting